Identification and Validation of a Core Single-Nucleotide Polymorphism Marker Set for Genetic Diversity Assessment, Fingerprinting Identification, and Core Collection Development in Bottle Gourd - Wang, Ying; Wu, Xiaohua; Li, Yanwei; Feng, Zishan; Mu, Zihan; Wang, Jiang; Wu, Xinyi; Wang, Baogen; Lu, Zhongfu; Li, Guojing (Frontiers in Plant Science, 2021)
Germplasm collections are indispensable resources for the mining of important genes and variety improvement. To preserve and utilize germplasm collections in bottle gourd, we identified and validated a highly informative core SNP marker set from 1100 SNPs. This marker set consisted of 22 uniformly distributed core SNPs with abundant polymorphisms, which were established to have strong representativeness and discriminatory power based on analyses of 206 bottle gourd germplasm collections and a multiparent advanced generation inter-cross (MAGIC) population. The core SNP markers were used to assess genetic diversity and population structure, and to fingerprint important accessions, which could provide an optimized procedure for seed authentication. Furthermore, using the core SNP marker set, we developed an accessible core population of 150 accessions that represents 100% of the genetic variation in bottle gourds. This core population will make an important contribution to the preservation and utilization of bottle gourd germplasm collections, cultivar identification, and marker-assisted breeding.